Jobs people do - Maynard, Christopher; DK Publishing, Inc. (New York : DK Pub., 1997)
Text and photographs of real people at work as well as authentic detailed costumes present the key aspects of over fifty occupations.
Includes index.
Booklist.
Catholic Library World.
Science Books & Films (A.A.A.S.).
2.4.
2.4
Keywords: Occupations -- Juvenile literature; Professions -- Juvenile literature; Vocational guidance -- Juvenile literature; Occupations; Vocational guidance; Occupations; Professions; Vocational guidance